2013
DOI: 10.1371/journal.pone.0054997
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Diversity in the Modern Horse Illustrated from Genome-Wide SNP Data

Abstract: Horses were domesticated from the Eurasian steppes 5,000–6,000 years ago. Since then, the use of horses for transportation, warfare, and agriculture, as well as selection for desired traits and fitness, has resulted in diverse populations distributed across the world, many of which have become or are in the process of becoming formally organized into closed, breeding populations (breeds). This report describes the use of a genome-wide set of autosomal SNPs and 814 horses from 36 breeds to provide the first det… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

31
267
6
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 213 publications
(307 citation statements)
references
References 68 publications
31
267
6
3
Order By: Relevance
“…By comparing genetic information of ancient and modern domesticated horses, we could pinpoint the genetic changes associated with domestication shared by all modern breeds. This methodology contrasts with scans for outlier genomic regions among modern breeds (35), which can, at best, identify genes that are specific to breeds, in the absence of knowledge of the predomesticated genetic background and sources of variation.…”
Section: Resultsmentioning
confidence: 99%
“…By comparing genetic information of ancient and modern domesticated horses, we could pinpoint the genetic changes associated with domestication shared by all modern breeds. This methodology contrasts with scans for outlier genomic regions among modern breeds (35), which can, at best, identify genes that are specific to breeds, in the absence of knowledge of the predomesticated genetic background and sources of variation.…”
Section: Resultsmentioning
confidence: 99%
“…Our laboratory conducted a CNV‐based GWAS by applying the aforementioned equine exon tilling array71 to the 72 foals studied in our SNP GWAS 48. Although similar lengths and numbers of CNVs were observed in these foals as in the previous report using this array, no CNVs were significantly associated with R. equi pneumonia in these foals.…”
Section: Copy Number Variantsmentioning
confidence: 63%
“…Furthermore, the longer the LD of the species the fewer SNPs are necessary to identify significant associations. Estimates of LD for breeds of horses are markedly longer than those for humans 48, 49. Thus, one might expect to need fewer SNPs on an equine array to have the same discriminatory power as a human array or to have greater power in a GWAS for horses than humans for an array of the same size or density of SNPs.…”
Section: Genome‐wide Association Studiesmentioning
confidence: 99%
“…Petersen et al (2013), using whole-genome single-nucleotide polymorphism data, suggested that horse breeds with low within-breed diversity, such as Thoroughbred and Quarter Horse, may be related to population bottlenecks, intense selective pressure or closed conditions due to their long breed histories. For the Thoroughbred breed, they reported a high mean individual inbreeding coefficient (larger than 10 %) (Petersen et al, 2013). In the present study, high heterozygosis showed no current inbreeding risk.…”
Section: Discussionmentioning
confidence: 99%